Polo-Like Kinase 1 Is Essential for Early Embryonic Development and Tumor Suppression - Lu, Lin-Yu (American Society for Microbiology (ASM), 2008)
Polo-like kinases (Plks) are serine/threonine kinases that are highly conserved in organisms from yeasts to humans. Previous reports have shown that Plk1 is critical for all stages of mitosis and may play a role in DNA replication during S phase. While much work has focused on Plk1, little is known about the physiological function of Plk1 in vivo. To address this question, we generated Plk1 knockout mice. Plk1 homozygous null mice were embryonic lethal, and early Plk1(−/−) embryos failed to survive after the eight-cell stage. Immunocytochemistry studies revealed that Plk1-null embryos were arrested outside the mitotic phase, suggesting that Plk1 is important for proper cell cycle progression. It has been postulated that Plk1 is a potential oncogene, due to its overexpression in a variety of tumors and tumor cell lines. While the Plk1 heterozygotes were healthy at birth, the incidence of tumors in these animals was threefold greater than that in their wild-type counterparts, demonstrating that the loss of one Plk1 allele accelerates tumor formation. Collectively, our data support that Plk1 is important for early embryonic development and may function as a haploinsufficient tumor suppressor.